Flavonoides en Musgos: consideraciones quimiosistemáticas. - López-sáez, José Antonio; Velasco-negueruela, Arturo; Pérez-alonso, María José (Botanica Complutensis, 1996)
LÓ¡±z-SÁEZ,JA.. M.J. PÉREZ-ALONSO & A. VELASCO NEGIJERUELA. 1996. Flavonoids in Musci: cheinosystemarie eonsiderations. Bat. Complutensis 21: 9-38. Tbk work confirnis that mosses are not primitive embryo-ptants. They are closely related tovaseu¡ar plants, aecording to their flavonoid counposition.